LIGHT SENSING TECHNOLOGY INNOVATION (LI-FI) AS AN ALTERNATIVE WIRELESS COMMUNICATION SOLUTION - Bambang Winardi; Thiago Rocha; Tanwir Tanwir (Journal of Moeslim Research Technik, 2025)
The increasing demand for high-speed wireless communication has led to the exploration of alternative technologies beyond traditional Wi-Fi. Light Fidelity (Li-Fi) technology, which utilizes visible light for data transmission, presents a promising solution to enhance wireless communication capabilities while alleviating congestion in radio frequency spectrum. This research aims to evaluate the effectiveness of Li-Fi as an alternative wireless communication method. The study focuses on analyzing data transmission rates, coverage areas, and potential applications of Li-Fi technology in various environments. An experimental approach was employed, involving the design and implementation of a Li-Fi system using LED lights for data transmission. Performance metrics, including data throughput and signal stability, were measured under different lighting conditions and distances. Comparative analysis with traditional Wi-Fi systems was conducted to assess the advantages and limitations of Li-Fi. The findings indicated that Li-Fi technology achieved data transmission rates exceeding 1 Gbps under optimal conditions, significantly outperforming conventional Wi-Fi in terms of speed. Coverage was effective within a range of 10 meters, with stable performance in various indoor environments. The results highlight Li-Fi's potential for applications in high-density areas, such as offices and hospitals. Li-Fi technology emerges as a viable alternative for wireless communication, offering high-speed data transmission and reduced interference.